2001
DOI: 10.1038/sj.sc.3101090
|View full text |Cite
|
Sign up to set email alerts
|

Vesico-ureteric reflux in adults with neuropathic bladders treated with Polydimethylsiloxane (Macroplastique®)

Abstract: Objective: To establish the ecacy of Macroplastique 1 in treating vesico-ureteric re¯ux (VUR) in adults with neuropathic bladder dysfunction. Patients and methods: Fifteen patients (12 male and three female), age range 19 to 80 years (mean age 38) were included in this study. Diagnosis was con®rmed by videourodynamics. In seven patients re¯ux was present bilaterally. Twenty-two re¯uxing ureters were treated. Twelve patients had detrusor hyper-re¯exia, two had are¯exic bladders and one had loss of bladder wall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…reported complete resolution of VUR after ESI in five (63%) of eight adults with neuropathic bladder caused by spinal cord injury. Shah et al 10 . reported the outcomes of ESI for 22 ureter units with neuropathic bladder.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…reported complete resolution of VUR after ESI in five (63%) of eight adults with neuropathic bladder caused by spinal cord injury. Shah et al 10 . reported the outcomes of ESI for 22 ureter units with neuropathic bladder.…”
Section: Discussionmentioning
confidence: 99%
“…VUR resolved in 72.2% (16 ureters) following a single injection. The authors suggested that ESI could be used as the first‐line treatment for VUR in adults with neurogenic bladder 10 . Diverse pathological conditions may cause neurogenic bladder dysfunction, and the physiological and functional changes may vary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macroplastique with dosage variable (0.7-1.5 ml) was injected submucosally under each ureteric orifice to convert the opening to a slit-like shape. 11,12 One-month post-treatment, new videourodynamics showed that all VUR had disappeared. Only one patient with SS-SCL was retreated with Macroplastique for recurrence of monolateral VUR (grade II) 1-year after the first treatment.…”
Section: Detrusor Acontractility or Underactivitymentioning
confidence: 99%